PENGENALAN MEDIA TANAM ALTERNATIF HIDROGEL SEBAGAI PENAMBAH NILAI ESTETIKA DI YAYASAN “UNTUKMU SI KECIL” SUMBERSARI JEMBER - Hutami, Trapsila Siwi; Irsyadi, Muhammad Burhanuddin; Astuti, Sri Rejeki Dwi (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
Increasing environmental awareness needs to be done to maintain good air quality. This can be done through reforestation. Plant cultivation can use planting media other than soil by using hydrogel as an alternative media which can add aesthetic value and economic value. A sense of environmental concern can be developed from an early age. The children at the